The use of Mediated Learning Experience for developing context and observation skills in scientific education (Olhar de Professor, 2024)
This article aimed to analyze the use of Mediated Learning Experience, according to Feuerstein (1990), for the development of two fundamental competencies in scientific education: context and observation, in two classes of the sixth grade in a public state school in Londrina-PR in 2023. The qualitative paradigm was employed in the investigative process. It is important to highlight that this work is a segment of a set of pedagogical sequences designed for the development of the first author's thesis. Thus, the didactic sequence was implemented with 47 students, and their productions were subsequently systematized and analyzed following Yin's (2016) guidelines. The results obtained for the students' basic competencies were as follows: context 91.48% and observation 80.84%. These results indicate that Mediated Learning Experience was significant for the development of these fundamental cognitive abilities within the theoretical and empirical limits of this study.
Keywords: Feuerstein; Science Education; Cognitive Operations